UPAYA MENCIPTAKAN BIROKRASI YANG EFISIEN, INOVATIF, RESPONSIF DAN AKUNTABEL - Haryanto, Aris Tri (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2007)
ABSTRACT Â  Bureaucracy in Indonesia at a period of new order inspired many by Weber bureaucracy principle. Principal applying of bureaucracy which ought to be convergent to serve society without reference to who is served, exactly bear bureaucracy disease pursuing fluency in serving society which is very leave for back from Weber bureaucracy idea. Reform Bureaucracy do not only limited to structure, just procedure or process but also moral reform and attitude all bureaucrat. Without there awareness to lessen or vanish various bureaucracy pathology form, hence reform in order to creating efficient bureaucracy, innovative, responsive and can be justified will only limited to statement. Keywords: bureaucracy, autonomous, organization.